Effect of long-term fertilization on soil aggregate-associated dissolved organic nitrogen on sloping cropland of purple soil - K.K. Hua; B. Zhu; X.G. Wang; X.S. Guo; D.Z. Wang; Z.B. Guo (Plant, Soil and Environment, 2014)
To investigate the effect of fertilization practice on dissolved organic nitrogen (DON) in aggregates, the study was conducted and involved four fertilization treatments: no fertilizer; mineral fertilizer (MF); pig manure matched with mineral fertilizer (MFP) and crop straw matched with mineral fertilizer (MFR). The results showed that DON content and storage were the highest in > 5 mm aggregates and were the lowest in < 0.25 mm aggregates. Compared with MF, MFP and MFR significantly increased DON contents in > 5 mm by 404.7% and 184.4%. In comparison with MFR, DON content and storage in > 5 mm aggregates for MFP were significantly enhanced by 77.5% and 75.0%. A significantly positive linear correlation relationship between DON content and microbial biomass carbon content was observed in aggregates (R2 = 0.84; P < 0.01). The results suggest that pig manure matched with mineral fertilizer is a preferred strategy for retaining DON nutrient due to enhanced microbial biomass in aggregates on sloping upland of purple soil.